De indígenas y cascabeles: aproximación a los recorridos y valoraciones de un objeto sonoro en Hispanoamérica colonial (siglos XVI-XVII) - Laura Fahrenkrog (Nuevo mundo - Mundos Nuevos, 2025)
In the 16th and 17th centuries, cascabeles (rumbler bells) rang and circulated in the hands of indigenous peoples from the Caribbean to the southernmost regions of the American continent. They were crafted from a variety of materials, including snails, nuts, and metal alloys. They were used in ritual and festive contexts, as well as for decorative purposes. In the early interactions between Europeans and Indigenous peoples in the Americas, these sonorous artifacts emerged as central and facilitators of encounters. European bells were quickly accepted and integrated into indigenous practices. As chronicles and documents show, they circulated from Europe to the Americas and between different regions of the New World. In these exchanges, the value attached to these objects acquired multiple meanings. This perspective has been little explored, and this article aims to approach it by studying documentary sources such as wills, inventories, and chronicles to elucidate the forms of circulation and valuation of rumbler bells by indigenous peoples in colonial Spanish America.